Political Strategy In Local Elections: Study Of Bandung Municipality Mayor General Election In 2003 And 2008 - MUFTI, MUSLIM (Jurnal Studi Pemerintahan, 2019)
This study aims to analyze the political strategies of actors in the 2008 election of the mayor of Bandung. Research location in Bandung Municipality, West Java Province. The research uses qualitative methods. The results of the study show that the election victory through political strategies can be won by the ability of actors who act as patrons to gain strength in gaining votes. In the indirect election, which was chosen by the Bandung Municipal Regional Legislative Council (DPRD) in 2003. Although the Golongan party of Dada Rosada was in third place, it was a very influential figure in Dada Rosada in bureaucrats, government and politicians using political network strategy to convince political party elites, so as to convince the party of the Indonesian Democratic Party of Struggle (PDI Perjuangan) and the National Mandate Party (PAN) which is in first and second positions. The post-reform political strategy was different from before the reforms determined by the centre, so the role of political actors was very decisive in the 2003 Bandung municipal elections which were elected through the Regional Legislative Council (DPRD). In 2008 Dada Rosada not only used political network strategies to convince political elites but also used social network strategies to gain support and sympathy for the people of Bandung. Because in 2008 the Bandung Regional Head Election (Pilkada) was directly elected by the community.Â